Balance of the labor process thirteen years after the entry into force of the New Labor Procedure Law - Quispe Montesinos, Carlos Alberto (2023)
The author analyzes the different innovations that have been taking place in the labor process. He evaluates the practices and experiences implemented in response to the COVID-19 pandemic and their compatibility with the model provided for by the New Labor Procedure Law. The author addresses the recent reform of labor appeals before the Supreme Court and identifies problems in the decisions of the Supreme Court to establish procedural rules through plenary agreements.